Microscopic and molecular identification of foreign matter in food: detection of fraudulent practices Identification of foreign matter: food fraud - Maria Aparecida Moraes Marciano; Maria Isabel Andrekowisk Fioravanti; Elaine Marra de Azevedo Mazon; Sheila Oliveira de Souza Silva; Paulo Eduardo Brandão; Simone de Carvalho Balian (Fundação Oswaldo Cruz (FIOCRUZ), 2018)
Introduction: The most frequent demands on microscopic food analysis are allegations of consumers finding macroscopic foreign matter or suspecting the presence of undeclared ingredients on products labels. The byproducts and foreign matters detection are fundamental practice for indirectly verifying the conditions of food production. Objective: This study reports the processes of microscopic and molecular identification (PCR) of a foreign matter found in a meat pie after a consumer complaint, occurred in the city of Itapira, state of São Paulo, Brazil. Method: Two distinct procedures were used to identify foreign matter: macroscopic examination, following FDA standards, and polymerase chain reaction (PCR) technique to identify DNA extracted from foreign materials. Results: The macroscopic analysis identified animal taste buds composing the pie fillings, and the PCR test confirmed that they were of bovine origin. Conclusions: Macroscopic analysis and the PCR test allowed the identification of the type of foreign matters and confirmed its bovine origin, what was enough to characterize it as a fraud by the improper use of inferior tissues in the preparation of ready-to-eat pastry.